Designing Fe2O3-Ti as Photoanode in H-Type Double-Electrode Coupling Systems for Bidirectional Photocatalytic Production of H2O2 - Danfeng Zhang; Changwei An; Dandan Liu; Tong Liu; Te Wang; Min Wang (Molecules)
Developing high-efficiency photoelectrodes plays an important role in the photoelectrocatalytic generation of hydrogen peroxide (H2O2) in the photoelectrochemical (PEC) water splitting field. In this work, an innovative strategy was proposed, the synergistic photocatalytic production of H2O2 using a bidirectional photoanode–photocathode coupling system under visible-light irradiation. Fe2O3-Ti, as the photoanode, which was built by way of Fe2O3 loaded on Ti-mesh using the hydrothermal-calcination method, was investigated in terms of the suitability of its properties for PEC H2O2 production after optimization of the bias voltage, the type of electrolyte solution, and the concentration of the electrolyte. Afterwards, a H-type double-electrode coupling system with an Fe2O3-Ti photoanode and a WO3@Co2SnO4 photocathode was established for the bidirectional synergistic production of H2O2 under visible-light irradiation. The yield of H2O2 reached 919.56 μmol·L−1·h−1 in 2 h over −0.7 V with 1 mol·L−1 of KHCO3 as the anolyte and 0.1 mol·L−1 Na2SO4 as the catholyte (pH = 3). It was inferred that H2O2 production on the WO3@Co2SnO4 photocathode was in line with the 2e- oxygen reduction reaction (ORR) principle, and on the Fe2O3-Ti photoanode was in line with the 2e- water oxidation reaction (WOR) rule, or it was indirectly promoted by the electrolyte solution KHCO3. This work provides an innovative idea and a reference for anode–cathode double coupling systems for the bidirectional production of H2O2.